Investigation of aging performance of bio‐oil phenol‐formaldehyde resin with the treatment of artificial accelerated aging method. Issue 10 (23rd December 2017) - Yu, Yuxiang; Xu, Pingping; Xing, Jingchen; Li, Lufei; Chang, Jianming
Abstract : The aging performance of bio‐oil phenol‐formaldehyde (BPF) resin was investigated using artificial accelerated aging method. After the treatment, the variations on the mass and bonding strength of plywood with BPF resin were determined. The changes in the microstructure, functional groups, and chemical bonds of adhesive films with BPF resin were also analyzed by scanning electron microscope, Fourier transform infrared spectroscopy, and X‐ray photoelectron spectroscopy analysis. The decrease of mass loss and bonding strength of BPF resin were smaller, the surface of BPF resin was smoother, and the amounts of CH2 groups and COC groups of BPF resin were larger than that of phenol‐formaldehyde (PF) resin at the same aged period. These results indicated that the bio‐oil could be used to improve the aging performance of PF resin. POLYM. ENG. SCI., 58:1810–1816, 2018. © 2017 Society of Plastics Engineers